2019
DOI: 10.7717/peerj.7248
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the erythrocyte phenotype and blood biochemistry in dairy calves during the first ten weeks of age

Abstract: BackgroundBovine erythrocytes undergo important changes in their morphology and chemical composition during the first weeks of age, which must be understood to accurately interpret hematology results in calves. The objectives of this prospective cohort study were to describe physiological changes of calf erythrocytes and to investigate mechanisms potentially causing these changes.MethodsBlood samples from 30 clinically healthy dairy calves were obtained from birth to the tenth week of age in weekly intervals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…However, administration of Se in the form of sodium selenite at dose of 2.5 mg/kg for 21 days and 0.25 mg/kg for 16 weeks induced acute and chronic selenosis in calves with significant decreased of total number of RBC and WBC as well as HGB concentration [ 23 ]. Some age-related physiological changes in the haemogram were observed in the present study, similarly to data obtained by other authors [ 20 ]. The reduction in RBC volume observed is related to the maturation of blood cells as the calves get older [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, administration of Se in the form of sodium selenite at dose of 2.5 mg/kg for 21 days and 0.25 mg/kg for 16 weeks induced acute and chronic selenosis in calves with significant decreased of total number of RBC and WBC as well as HGB concentration [ 23 ]. Some age-related physiological changes in the haemogram were observed in the present study, similarly to data obtained by other authors [ 20 ]. The reduction in RBC volume observed is related to the maturation of blood cells as the calves get older [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Arthur [ 19 ] explained this period by the mechanisms of selenium incorporation into erythrocytes during erythropoiesis and the time necessary for the biosynthesis of the enzyme itself. It should be noted that during the monitoring period of this study (0–14 days of age) foetal erythrocytes comprised the majority of the calves’ red cell population, being replaced by adult erythrocytes by eight to 13 weeks of age [ 20 ]. Though it should be recognised that this conversion from foetal to adult haemoglobin is a dynamic process which would have already commenced during the monitored response period of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with observations of Dillane et al ( 46 ) for Cl − , PCV, and pH (which showed a tendency), are contrary for Na + , and are not coincident for glucose, HCO , PCO 2 , AG, and K + (not affected by sex in our study). Other studies did not find differences attributable to calf sex for the above and other parameters investigated ( 76 , 90 ).…”
Section: Discussionmentioning
confidence: 60%
“…Embryo cryopreservation did not interfere with this normal adaptation to adult life. Consistent with sO 2 , PCV values decreased throughout, reflecting the physiological replacement of large fetal erythrocytes by the lower volume adult cells ( 76 ). At the end of pregnancy, the fetus responds to hypoxia with a transient higher concentration of Hb and PCV.…”
Section: Discussionmentioning
confidence: 65%
“…Wise et al (1947) e Tennant et al (1974) reportaram que o declínio do VCM em bezerros neonatos é um processo fisiológico e conforme Jain (1993) coincide a substituição dos eritrócitos e hemoglobina fetais por células de adultos (menores). O declínio observado é consistente com observações de Golbeck et al (2019) sobre o desenvolvimento de anemia microcítica leve, que, se associada à hipocromia caracteriza deficiência de ferro, sendo esperada anemia em 20 a 30% dos bezerros.…”
Section: Resultsunclassified